2014
DOI: 10.1097/id.0000000000000048
|View full text |Cite
|
Sign up to set email alerts
|

Implants for Orthodontic Anchorage

Abstract: Mini-implant survival rate is location dependent, with those placed in the palate showing higher success rates. In addition, failures most commonly occur because of surgery-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Their convenience, simplicity and superior performance compared with conventional methods have contributed to their wide acceptance [ 7 ]. Several systematic reviews had shown the overall failure rates for OMIs with further exploration of the potential factors contributing to their failure [ 8 11 ]. However, OMIs could be placed in various insertion sites, and every one of those has its potential anatomical advantages and limitations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their convenience, simplicity and superior performance compared with conventional methods have contributed to their wide acceptance [ 7 ]. Several systematic reviews had shown the overall failure rates for OMIs with further exploration of the potential factors contributing to their failure [ 8 11 ]. However, OMIs could be placed in various insertion sites, and every one of those has its potential anatomical advantages and limitations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…malocclusion cases. According to clinical research [3][4][5], the current success rate for mini-implants and micro-implants of various designs and sizes is >80%. Orthodontic implants inserted into bones exhibit two types of stability: primary and secondary stability.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Albogha and Takahashi have stated a success rate ranging from 77.7% to 93.43% in their study [2]. However, the failure of miniscrew may have dramatic consequences and remain difficult to be anticipated by orthodontists [3]. Since the failure of miniscrew necessitates additional surgical interventions and prolonged treatment time, investigating the mechanical stability of miniscrew becomes imperative.…”
Section: Introductionmentioning
confidence: 99%
“…It is clinically evident that full osseointegration is a prerequisite for successful prosthetic (or dental) implants [4, 5]. Nevertheless, some fibrous tissue formation at the bone-implant interface would be acceptable because orthodontic loading has to be applied as early as possible and also the miniscrew at the end of treatment must be easily removable [3]. That is to say, partial bone-implant osseointegration of the miniscrew might be permitted for orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%